Understanding Education Workers' Stressors after Lockdowns in Ontario, Canada: A Qualitative Study - Frances Serrano; Marianne Saragosa; Behdin Nowrouzi-Kia; Lynn Woodford; Jennifer Casole; Basem Gohar (MDPI AG, 2023)
Understanding the experiences and stressors of education workers is critical for making improvements and planning for future emergency situations. Province-specific studies offer valuable information to understand the stressors of returning to the workplace. This study aims to identify the stressors education workers experienced when returning to work after months of school closures. This qualitative data is part of a larger study. Individuals completed a survey including a questionnaire and some open-ended questions in English and French. A total of 2349 respondents completed the qualitative portion of the survey, of which most were women (81%), approximately 44 years of age, and working as teachers (83.9%). The open-ended questions were analyzed using thematic analysis. Seven themes emerged from our analysis: (1) challenges with service provision and using technology; (2) disruption in work-life balance; (3) lack of clear communication and direction from the government and school administration; (4) fear of contracting the virus due to insufficient health/COVID-19 protocols; (5) increase in work demands; (6) various coping strategies to deal with the stressors of working during the COVID-19 pandemic; (7) lessons to be learned from working amid a global pandemic. Education workers have faced many challenges since returning to work. These findings demonstrate the need for improvements such as greater flexibility, training opportunities, support, and communication.